2023
DOI: 10.1051/0004-6361/202244331
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic-ray electron transport in the galaxy M 51

Abstract: Context. Indirect observations of the cosmic-ray electron (CRE) distribution via synchrotron emission is crucial for deepening the understanding of the CRE transport in the interstellar medium, and in investigating the role of galactic outflows. Aims. In this paper, we quantify the contribution of diffusion-and advection-dominated transport of CREs in the galaxy M51 considering relevant energy loss processes. Methods. We used recent measurement from M51 that allow for the derivation of the diffusion coefficien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…While our method is sensitive to smoothing of the Σ SFR map by CRE diffusion, the radio spectral index distribution is more governed by the escape of CRE from the galaxy. Our best-fitting diffusion coefficient of D ≈ 2 × 10 28 cm 2 s −1 is in good agreement with the results of Dörner et al (2023) but lower than the value by Mulcahy et al (2016), who found D ≈ 6 × 10 28 cm 2 s −1 . The difference can be mostly attributed to the fact that Mulcahy et al (2016) modelled CRE escape only via diffusion, whereas Dörner et al (2023) used a combination of diffusion and advection.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…While our method is sensitive to smoothing of the Σ SFR map by CRE diffusion, the radio spectral index distribution is more governed by the escape of CRE from the galaxy. Our best-fitting diffusion coefficient of D ≈ 2 × 10 28 cm 2 s −1 is in good agreement with the results of Dörner et al (2023) but lower than the value by Mulcahy et al (2016), who found D ≈ 6 × 10 28 cm 2 s −1 . The difference can be mostly attributed to the fact that Mulcahy et al (2016) modelled CRE escape only via diffusion, whereas Dörner et al (2023) used a combination of diffusion and advection.…”
Section: Discussionsupporting
confidence: 91%
“…Our best-fitting diffusion coefficient of D ≈ 2 × 10 28 cm 2 s −1 is in good agreement with the results of Dörner et al (2023) but lower than the value by Mulcahy et al (2016), who found D ≈ 6 × 10 28 cm 2 s −1 . The difference can be mostly attributed to the fact that Mulcahy et al (2016) modelled CRE escape only via diffusion, whereas Dörner et al (2023) used a combination of diffusion and advection. Consequently, the diffusion coefficient has to be higher in order to allow for a fast enough CRE escape (Mulcahy et al 2016).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations